Pengaruh Model Pembelajaran Inquiri Terbimbing Berbantuan Video Terhadap Sikap Ilmiah Dan Hasil Belajar Pada Konsep Usaha Dan Energi - Dewi Belinda; Tya Ayu Palupy (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of video-assisted guided inquiry learning model on scientific attitudes and learning outcomes in the concept of work and energy. This research was conducted by FKIP Elementary School Teacher Education Study Program, Pohuwato University in the 2024/2025 academic year with a sample of 50 students, consisting of 25 students in the experimental class and 25 people in the replication class. This study uses the method This study uses a